Investigation of Procedural Decisions at the Beginning of Pre-Trial Investigation (Bulletin of Kharkiv National University of Internal Affairs, 2020)
The author of the article studies one of the most important current topics from the point of view of practice – the decision of investigators to initiate a pre-trial investigation in criminal proceedings. It is emphasized that all further movement of criminal proceedings depends on the timeliness of the investigator’s decision to conduct a pre-trial investigation. Moreover, it is of great importance for the effective achievement of such a task of criminal proceedings as the speed and completeness of the investigation. It is determined that the guarantee of non-entry of information about a criminal offense in the Unified Register of Pre-trial Investigations is the right of the applicant to appeal against decisions, actions or omission of the investigator, prosecutor. At the same time, the absence of a legal requirement to make a procedural decision to initiate or to refuse a pre-trial investigation, in particular in the form of a ruling, does not always contribute to the exercise of the applicant’s right to appeal. It is confirmed by the relevant court decisions, which, unfortunately, currently takes place in practice. Based on the results of the study, possible ways to improve the current criminal procedural legislation of Ukraine on this issue are proposed.The author has determined that the adoption of a procedural decision is impossible without a mandatory component of such a mechanism as the subject endowed with the relevant powers, and the quality of the decision itself directly depends on professional competence. The investigator, being authorized to conduct criminal proceedings, is an official who exercises state power through the adoption of procedural decisions, which affects the further direction of criminal proceedings.It is emphasized that the content of the procedural decision of the investigator, in a broad sense, is a product of mental activity, which forms the basis for the tasks of criminal proceedings.It is concluded that the investigator’s decision in the form of a reasoned decision to initiate or to refuse a pre-trial investigation is quite logical. It is explained by the fact that, first of all, the decision is an official written response to the appeal. It is established that early receipt of the decision is a guarantee of the right to appeal against decisions, actions or omission of the pre-trial investigation agencies.